ADJUSTABLE COMPONENTS IN AUTOMATED CONTROL SYSTEMS OF NPP TECHNOLOGICAL PROCESSES - Ukhina, H. V.; Bilenko А. А.; Sytnikov, V. S. (Вісник Черкаського державного технологічного університету, 2018)
Transfer function coefficients’ effect on the properties of amplitude-frequency characteristic, which should be taken into account at adjustable components designing, is considered. On the example of typical digital filters of the first order of low and high frequencies, the dependencies of the transfer function’s numerator and denominator coefficients on the cutoff frequency, as well as the denominator coefficient’s dependence on the ripple index are found.